Guideline for standardized approach in the treatment of the Mal de Debarquement syndrome - Schoenmaekers, Catho; Jillings, Steven; De Laet, Chloë; Zarowski, Andrzej; Wuyts, Floris L. (Frontiers in Neurology, 2024)
Introduction Mal de Debarquement Syndrome (MdDS) is a debilitating neuro-otological disorder. Patients experience almost continuously a perception of self-motion. This syndrome can be motion-triggered (MT-MdDS), such as on a boat, or occur spontaneously or have other triggers (SO-MdDS) in the absence of such motion. Because the pathophysiological mechanism is unknown, treatment options and symptom management strategies are limited. One available treatment protocol involves a readaptation of the vestibular ocular reflex (VOR). This study assesses the effectiveness of vestibulo-ocular reflex (VOR) readaptation in 131 consecutive patients with a fixed protocol. Methods We administered 131 treatments involving optokinetic stimulation (OKS) paired with a fixed head roll at 0.167 Hz over two to five consecutive days. Each day, four-minute treatment blocks were scheduled twice in the morning and afternoon. Treatment effectiveness was evaluated through questionnaires and posturography. Results We observed significant improvements in the visual analog scale (VAS), MdDS symptom questionnaire, and posturography measures from pre- to post-treatment. No significant differences were found in outcome variables between MT- and SO-MdDS onsets. Conclusion Symptoms improved subjectively and objectively in patients’ post-treatment. The overall success rate was 64.1%, with no significant difference between MT (64.2%) and SO (63.3%). This study supports the conclusion that VOR readaptation treatment provides relief for two-thirds of MdDS patients, irrespective of the onset type. Based on consistency in the findings, we propose a standardized method for treatment of MdDS based on the OKS with head roll paradigm.